(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the pedagogical possibilities of distance learning in the higher education system, its role in the modern educational process, its advantages and practical significance. In the current era of rapid development of digital technologies, distance learning is emerging as an important pedagogical tool that allows expanding educational services, flexibly organizing the teaching process, activating students’ independent learning activities, and strengthening an individual approach. The article covers the essence of distance learning, didactic foundations, pedagogical principles, interactivity, individualization, differentiation, independent learning, reflection, and control. It also explains the role of electronic platforms, digital resources, video lessons, forums, testing systems, and virtual collaboration tools in organizing distance learning. The study concludes that distance learning can serve to increase the quality, convenience, and scope of education in the higher education system, but it also justifies the need for pedagogical design, digital competence, and motivational support for its effective use.